IMPLEMENTASI MEDIA DIGITAL BERBASIS POWER POINT DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Nurul Khotimah; Nania Wahyuni; Adrias; Nur Azmi Alwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Technological developments provide opportunities for teachers to innovate in learning, especially in natural science subjects in elementary schools. The purpose of this article is to determine the benefits that can be obtained from the use of PowerPoint, the challenges that teachers may face, and the steps teachers take to overcome these challenges. This study uses a qualitative approach with a descriptive research type. The research subjects consisted of teachers and fifth-grade elementary school students. Data collection techniques were carried out through learning observations, interviews with teachers, and documentation of learning activities. The results of this study indicate that digital learning media based on PowerPoint has its own benefits in improving the quality of science learning in elementary schools and needs to be supported by improving teachers' technological competence and optimizing digital learning facilities.